2009
DOI: 10.1098/rspb.2009.1373
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transmission as the key to the colonization of Madagascar by fungus-growing termites?

Abstract: The mutualism between fungus-growing termites (Macrotermitinae) and their mutualistic fungi (Termitomyces) began in Africa. The fungus-growing termites have secondarily colonized Madagascar and only a subset of the genera found in Africa is found on this isolated island. Successful long-distance colonization may have been severely constrained by the obligate interaction of the termites with fungal symbionts and the need to acquire these symbionts secondarily from the environment for most species (horizontal sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 36 publications
2
71
0
Order By: Relevance
“…Such long-distance dispersal ability of Attamyces would contrast with the dispersal ability of Termitomyces fungi of the termiteTermitomyces symbiosis, in which effective long-distance dispersal of Termitomyces across oceanic barriers appears to be rare (e.g. between mainland Africa and Madagascar [60]). However, long-distance dispersal and genetic mixing of Attamyces could help explain the much younger coalescence and origin of Attamyces fungi (about 2-4 Myr old) compared with the corresponding origin of leaf-cutter ants (about 8 -12 Myr old) [40].…”
Section: Discussionmentioning
confidence: 99%
“…Such long-distance dispersal ability of Attamyces would contrast with the dispersal ability of Termitomyces fungi of the termiteTermitomyces symbiosis, in which effective long-distance dispersal of Termitomyces across oceanic barriers appears to be rare (e.g. between mainland Africa and Madagascar [60]). However, long-distance dispersal and genetic mixing of Attamyces could help explain the much younger coalescence and origin of Attamyces fungi (about 2-4 Myr old) compared with the corresponding origin of leaf-cutter ants (about 8 -12 Myr old) [40].…”
Section: Discussionmentioning
confidence: 99%
“…Island angiosperms are predominantly pollinated by wind or generalist insects and depend on generalist vertebrates for fruit dispersal [4]. Difficulties of synchronous co-establishment are thought to also restrict island colonization by plants or animals that require specialized fungal symbionts [5,6]. Alternatively, specialized mutualisms may be lost when plants colonize islands in the absence of mutualists [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, such a pattern has been observed in several studies. For example, the single colonization of Termitomyces fungi in Madagascar was likely established through this mechanism (Nobre 2010a; Nobre et al 2010b). In addition, Nobre et al (2011b) found that the genetic structure of symbiotic fungi of Macrotermes bellicosus is consistent with clonal reproduction with limited evidence for recombination (Table1).…”
Section: Macrofungi In Mutualistic Relationships With Animalsmentioning
confidence: 99%